Validation of natural language processing methods capturing semantic incoherence in the speech of patients with non-affective psychosis - Just, Sandra Anna; Bröcker, Anna-Lena; Ryazanskaya, Galina; Nenchev, Ivan; Schneider, Maria; Bermpohl, Felix; Heinz, Andreas; Montag, Christiane (Frontiers in Psychiatry, 2023)
This study aimed to validate methods of natural language processing for analyzing speech production in patients with non-affective psychosis (NAP). Global and local models of semantic coherence as well as different word embeddings (word2vec vs. GloVe) were tested and compared regarding their correlation with clinical ratings and external criteria from cross-sectional and longitudinal measurements. Results did not show differences for global vs. local coherence models and indicated that word2vec models might outperform GloVe models as they seemed to be more often associated with clinically relevant outcomes. Exploratory analysis of longitudinal data did not yield significant correlation with coherence scores. These results indicate that natural language processing methods need to be critically validated in more studies and carefully selected before clinical application.